15+4n=7(2n+3)-6

Simple and best practice solution for 15+4n=7(2n+3)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15+4n=7(2n+3)-6 equation:


Simplifying
15 + 4n = 7(2n + 3) + -6

Reorder the terms:
15 + 4n = 7(3 + 2n) + -6
15 + 4n = (3 * 7 + 2n * 7) + -6
15 + 4n = (21 + 14n) + -6

Reorder the terms:
15 + 4n = 21 + -6 + 14n

Combine like terms: 21 + -6 = 15
15 + 4n = 15 + 14n

Add '-15' to each side of the equation.
15 + -15 + 4n = 15 + -15 + 14n

Combine like terms: 15 + -15 = 0
0 + 4n = 15 + -15 + 14n
4n = 15 + -15 + 14n

Combine like terms: 15 + -15 = 0
4n = 0 + 14n
4n = 14n

Solving
4n = 14n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-14n' to each side of the equation.
4n + -14n = 14n + -14n

Combine like terms: 4n + -14n = -10n
-10n = 14n + -14n

Combine like terms: 14n + -14n = 0
-10n = 0

Divide each side by '-10'.
n = 0.0

Simplifying
n = 0.0

See similar equations:

| -8y+6(y-4)=-18 | | 30x+60y=100 | | 2w-1=-6w+15 | | x+1=19+2x-4+7x+11 | | 3(4n+5)+8n= | | 0=q^2-4q-20 | | -2=5u-7 | | 4(2b+5)=52 | | 1/6x72 | | 2x+80= | | 5x-2y+5x-2y=20 | | n-14+8n= | | -19(13-17x)= | | 8x+12+9x= | | 5m(2n-7)= | | (2x+20)+(6x+40)=180 | | -7(a+7)=-5(4a+6)-6a | | 12+3(4x-6y)-8y= | | 0.50x+0.6=0.3x-1.5 | | 5x^3+14x^2+8x=0 | | (x-(4+3i))(x-(4-3i))=0 | | x^2=-4x+400 | | 3=m/6 | | 3x^4-1=0 | | h=-16t^224*t-3 | | a+2.75+9.35+(2a+2.75+9.35)*0.0715=261.76 | | 2u-4u=-13+11 | | 6(2y+5)-2y+10= | | a+3+9.35+(2a+3+9.35)*0.0715=261.76 | | 3(x-4)=2-2(6-x) | | u^2-10u-9=0 | | -2(m-4)=7m+4(2+7m) |

Equations solver categories